Formulation of metaheuristic algorithms based on artificial bee colony for engineering problems - Lee, Wei Wen (2024)
The Artificial Bee Colony (ABC) algorithm is a powerful metaheuristic optimization technique inspired by the honeybee foraging behaviour. However, ABC algorithm can struggle to explore new regions effectively, leading to slow convergence and premature convergence on suboptimal solutions. This research addresses these limitations by developing modified ABC algorithms specifically for tackling engineering optimization problems. Recognizing limitations in the employed bee phase, the research applies the modification rate (